Alterations in gut microbiota improve SCFA production and fiber utilization in Tibetan pigs fed alfalfa diet - Gao, Qingtao; Sun, Guangming; Duan, Jiujun; Luo, Chengzeng; Yangji, Cidan; Zhong, Ruqing; Chen, Liang; Zhu, Yanbin; Wangdui, Basang; Zhang, Hongfu (Frontiers in Microbiology, 2022)
Tibetan pigs were thought to have good performances of rough feeding tolerance, which may be related to the gut microbiota. This study was conducted to investigate the changes of colonic microbiota contribute to fiber utilization in Tibetan pigs fed commercial diet or alfalfa supplementation diet, and verified whether the microbial community in Tibetan pigs fed alfalfa diet was beneficial to utilize fiber using in vitro fermentation. A total of 40 Tibetan pigs were allocated into two groups and fed with a corn-soybean meal basal diet (CD) or a 50% alfalfa supplementation diet (AD) for 42d. Our results showed pigs fed CD diet improved carcass weight compared to pigs fed AD diet (P < 0.05), whereas the bacterial diversity was decreased (P < 0.05). Tibetan pigs fed CD diet increased certain pathogenic bacteria (Streptococcus) abundance (FDR < 0.05). Alfalfa consumption increased fiber degrading bacteria abundance (UCG-005, Rikenellaceae_RC9_gut_group, Prevotellaceae_UCG-003, Alloprevotella, Marvinbryantia, and Anaerovibrio) in the colonic digesta (FDR < 0.05). Tibetan pigs received alfalfa improved concentrations of acetate, propionate, butyrate, and total SCFA in colonic content (P < 0.05). Higher fermentation capacity of fecal microbiota from pig fed AD diet was verified by in vitro fermentation. Collectively, our results indicated that alfalfa supplementation in diets improved the abundance of fiber-degrading bacteria and SCFA production in the hindgut of Tibetan pig, as well as enhanced the fermentation capacity of fecal microbiota.